Private and public liquidity provision in over-the-counter markets - David M. Arseneau; David E. Rappoport; Alexandros P. Vardoulakis (Theoretical Economics, 2020)
We show that trade frictions in OTC markets result in inefficient private liquidity provision. We develop a dynamic model of market-based financial intermediation with a two-way interaction between primary credit markets and secondary OTC markets. Private allocations are generically inefficient because investors and firms fail to internalize how their actions affect liquidity in secondary markets. This inefficiency can lead to liquidity that is suboptimally low or high compared to the second best, providing a rationale for the regulation and public provision of liquidity. Moreover, our model characterizes a transmission channel of quantitative easing or tightening operating through liquidity premia.
Keywords: E44; G18; G30; 330; Liquidity provision; market liquidity; over-the-counter markets; quantitative easing; quantitative tightening; monetary policy normalization